Pengaruh Komunikasi Efektif terhadap Kinerja Intelijen: Perspektif Bais - Rustam Rustam; Imam Munajat Nurhartonosuro; Muhadi Muhadi (Lembaga Kajian Pertahanan Strategis, 2024)
Effective communication plays a crucial role in intelligence operations, especially in the context of the State Intelligence Agency (BAIS). The ability to collect, analyze and disseminate information in a timely and accurate manner is a determining factor in supporting strategic decisions and responses to national security threats. This research aims to explore the influence of effective communication on intelligence performance at BAIS. The primary focus is to identify how good communications practices can improve the process of gathering, analyzing, and using intelligence information to support better strategic decisions. A quantitative approach was used by collecting data through questionnaires from 50 respondents who were members of BAIS. The questionnaire was designed to measure their perception of the quality of communication in the organization and its impact on intelligence performance. Regression analysis was used to evaluate the relationship between effective communication and intelligence performance. The results of the analysis show that there is a positive and significant relationship between effective communication and intelligence performance in BAIS (? = 0.72, p < 0.001). The high reliability of the measurement instruments (? = 0.87 for Effective Communication and ? = 0.83 for Intelligence Performance) validates the reliability of the data collected. The implications of this research highlight the importance of improving effective communication practices as a strategy to increase responsibility and performance in facing national security challenges.